Carbon stocks in Miombo Woodlands: Evidence from over 50 years - Bulusu, M.; Martius, C.; Clendenning, J. (MDPI, 2021)
Miombo woodlands are extensive dry forest ecosystems in central and southern Africa covering ≈2.7 million km2. Despite their vast expanse and global importance for carbon storage, the long-term carbon stocks and dynamics have been poorly researched. The objective of this paper is to present and summarize the evidence gathered on above- and belowground (root and soil) carbon stocks of miombo woodlands from the 1960s to mid-2018 through a review. We analyzed data to answer: (1) What is the range of aboveground and belowground carbon stocks found in miombo woodlands over the last six decades? (2) Are there differences in carbon stocks based on land-management categories? (3) Does precipitation influence aboveground carbon stocks in old-growth miombo? (4) Do differences in cover type, age and region influence carbon stocks? (5) How does previous land-use affect carbon stocks in re-growth miombo? A literature review protocol was used to identify 56 publications from which quantitative data on aboveground and soil carbon pools were extracted. We found that the mean aboveground carbon stock in old-growth miombo was 30.83±16.76 Mg C ha-1 (range 1.48—107.24 Mg ha-1). Old-growth miombo had an average calculated root carbon stock of 16.49±9.18 Mg C ha-1 (range 0.8—57.81 Mg ha-1). Soil carbon stocks in old-growth miombo varied widely, between 8.75 and 134.6 Mg C ha-1 while in re-growth miombo they varied between 10.73 and 52.2 Mg C ha-1. It must be noted these soil data are given only for information; they inconsistently refer to varying soil depths and are thus difficult to interpret. The wide range reported suggests a need for further studies, much more systematic in methods and reporting. Other limitations of the dataset include the lack of systematic sampling and lack of data in some countries, viz. Angola and Democratic Republic of the Congo.